Transitioning to sustainable energy - financing a major Caribbean challenge - Phillips, Willard (2016)
Examines the challenges faced by Caribbean Small Island Developing States (SIDS) in transitioning from their current dependence on imported fossil energy to greater efficiency in energy use, and a higher reliance on renewable energy sources.